PERANCANGAN CETAKAN PERMANEN CLAMPING CONNECTOR UNTUK LISTRIK TEGANGAN TINGGI - Kusuma, Andhika Aji (POLITALA PRESS, 2024)
This research focuses on the design of a clamping connector for high-voltage electrical systems using the permanent mold casting method. The design was developed using CAD/CAM software, with materials selected based on mechanical strength and temperature resistance. A prototype was created using CNC technology to ensure precision. The permanent mold design method was chosen to reduce production costs and improve efficiency without the need for welding processes. The results of the research indicate that this method produces clamping connectors that can be manufactured without the use of welding. The product design and permanent mold have been completed and are ready for production.